2006
DOI: 10.1007/11753681_22
|View full text |Cite
|
Sign up to set email alerts
|

Designing Nucleotide Sequences for Computation: A Survey of Constraints

Abstract: We survey the biochemical constraints useful for the design of DNA code words for DNA computation. We define the DNA/RNA Code Constraint problem and cover biochemistry topics relevant to DNA libraries. We examine which biochemical constraints are best suited for DNA word design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…To make a set of DNA sequences effective in DNA computing, they must fulfill a number of combinatorial and thermodynamic constraints. Such a task is not easy to achieve, and it has been shown that designing a set of good DNA sequences is an NP-hard (non-deterministic polynomial-time hard) problem [25,26].…”
Section: Citationmentioning
confidence: 99%
“…To make a set of DNA sequences effective in DNA computing, they must fulfill a number of combinatorial and thermodynamic constraints. Such a task is not easy to achieve, and it has been shown that designing a set of good DNA sequences is an NP-hard (non-deterministic polynomial-time hard) problem [25,26].…”
Section: Citationmentioning
confidence: 99%
“…References [87,98] and others distinguish two elementary subproblems of the encoding sequence design:…”
Section: Dna Encoding: Problem Setting and Notationmentioning
confidence: 99%
“…In contrast, the negative design problem can be solved on a general basis by construction of a library of molecules which do not allow for undesired mutual hybridizations. According to [98], the following conditions must be guaranteed: (1) no strand forms any undesired secondary structure such as hairpin loops ( Figure 9(a)), (2) no string in the library hybridizes with any string in the library, and (3) no string in the library hybridizes with the complement of any string in the library (Figure 9(b) or (c)). Many laboratory techniques stress the importance of a unified framework for the negative design.…”
Section: Dna Encoding: Problem Setting and Notationmentioning
confidence: 99%
“…As customary in formal models of DNA computing [21], each letter represents a domain, i.e., a string over the DNA alphabet {A, C, G, T }. The set of resulting domains must form a set of DNA codewords [11,27,31]. This should always be kept in mind.…”
Section: The Sticker-complex Data Modelmentioning
confidence: 99%